The impact of education through nurse-led telephone follow-up (telenursing) on the quality of life of COVID-19 patients - Rasoul Raesi; Zahra Abbasi Shaye; Sam Saghari; Mohammad Ali Sheikh Beig Goharrizi; Mehdi Raei; Kiavash Hushmandi (SpringerOpen, 2021)
Abstracts Background The widespread prevalence of COVID-19 has disrupted the social life, physical function, and daily activities of patients, leading to reduced quality of their lives. Because of the nature of this disease and its comprehensive impact on patients' lives, a follow-up based on the conditions of these patients is necessary. This study was conducted to determine the impact of nurse education and telephone follow-up (telenursing) on the quality of life of COVID-19 patients. Methods This quasi-experimental study included 120 COVID-19 patients discharged from 22nd-Bahman Hospital in Khaf city and was conducted over 6 months from July 20, 2020, to December 20, 2020. The participants were selected by convenience sampling method and were assigned into two matching groups. The training was delivered through telenursing based on the quality of life criteria for 1 month in the intervention group. The controls did not receive any intervention. Both groups completed the 36-item SF health survey before and 1 month after the intervention. Results The two groups were not significantly different regarding the quality of life mean scores at baseline (p = 0.61). However, after the intervention, the mean and standard deviation of the total life quality score was significantly different between the control and intervention groups (63.62 ± 3.93 versus 72.62 ± 3.51, p <0.001). Conclusions Telenursing improves the life quality of COVID-19 patients. Through appropriate policies, health managers may put on the agenda the implementation of telenursing for COVID-19 patients.